Modeling of the lifting of a heat transfer agent in a geothermal well of a gas condensate deposit - Fyk, M. I.; Biletskyi, V. S.; Abbood, Mohammed; Al-Sultan, Mohammed; Abbood, Majid; Abdullatif, Haval; Shapchenko, Yevhen (Національний технічний університет "Дніпровська політехніка", 2020)
Purpose is to develop mathematical model of nonisothermal inflow and lifting of the recovered gaseous mixture (i.e. geothermal fluid) of a well taking into consideration dynamic coefficient of heat transfer and thermal diffusion coefficient; fluid expansion coefficient in terms of nonadiabatic process; effect of average integral environmental temperature on the heat transfer coefficient; changes in molar mass of the fluid during the well operation; and a process of the productive seam cooling during initial development stages (i.e. months-years). Methods of material and energy balance of fluid-heat flows within a productive formation and within a well as well as forecasting of geothermal fluid production; numerical methods of fluid thermal gas dynamics; Runge-Kutta 4th order method; and Quazi-Newton method to solve nonlinear equations have been applied. Findings. It has been demonstrated that thermal gradient of rocks and thermal carrier-rock heat exchange vary depending upon operation modes of the formation and the well in terms of temperature effect, temperature difference in humidity, viscosity, compressibility, and other rock characteristics determining efficiency of thermal diffusion as well as coefficient of heat exchange between the fluid and rocks. Originality. The specified equations of thermal energy balance in terms of radial filtration and well product lifting have been developed. The equations are more preferable to compare with the current calculation technique, where a coefficient of fluid is expanded in a seam in the context of nonadiabatic process, and consideration of effect of average integral environment temperature of the heat transfer strength (the known methods takes into account geometric mean of the formation temperature). Actual changes in molar mass of the produced geothermal fluid during the whole period of the well operation (i.e. up to 50 years) are involved. Thermal gas dynamic model well inflow-lifting has been improved owing to the consideration of a transient process of the productive formation cooling during the initial stage of the geothermal fluid production (i.e. months-years). Practical implications. The developed mathematical model helps specify calculation of a well yield by 10-15%. To compare with the standard methods, the model makes it possible to perform 20-30% specification of heat output by a gas condensate well in terms of thermobaric intensification of the fluid production as well as in terms of binary techniques of fluidgeoheat generation.

Мета. Розробка математичної моделі неізотермічного притоку та ліфтингу видобувної газоподібної суміші (геотермального флюїду) свердловини з урахуванням динамічного коефіцієнта теплопровідності та теплової дифузії, коефіцієнта дроселювання флюїду при неадіабатичному процесі, впливу середньоінтегральної температури середовища на ефективність теплопередачі, зміни молярної маси флюїду протягом терміну експлуатації свердловини, процесу охолодження продуктивного пласта на первинному етапі (місяці – роки) експлуатації. Методика. Застосовано метод матеріально-енергетичного балансу потоків флюїду і тепла у продуктивному пласті та свердловині, прогнозування видобутку геотермального флюїду, чисельні методи термогазодинаміки рідини, методи Ранге-Кута четвертого порядку та Квазіньютонівський метод вирішення нелінійних рівнянь. Результати. Показано, що термічний градієнт гірських порід та теплообмін "теплоносій – порода" змінюється залежно від режиму роботи покладу та свердловини. Це обумовлюється впливом температури, перепаду температури на вологість, в’язкість, стисливість, інші властивості порід, які визначають ефективність теплової дифузії та коефіцієнт теплообміну між флюїдом та гірськими породами. Наукова новизна. Розроблено уточнені рівняння теплового балансу енергії при радіальній фільтрації та ліфтингу продукції свердловини, які вигідно відрізняються від застосовуваних в сучасних методах розрахунку введенням коефіцієнта дроселювання флюїду в пласті при неадіабатичному процесі, врахуванням впливу середньоінтегральної температури середовища на ефективність теплопередачі (відомі методики враховують середньогеометричну температуру пласта). Враховується фактична зміна молярної маси видобувного геотермального флюїду протягом терміну експлуатації свердловини (до 50 років). Термогазодинамічну модель "свердловинний притік – ліфтинг" вдосконалено врахуванням перехідного процесу охолодження продуктивного пласта на первинному етапі (місяці – роки) видобування геотермального флюїду. Практична значимість. Розроблена математична модель дозволяє уточнити розрахунок дебіту свердловини на 10-15%. Розроблена модель відносно базових методик дозволяє в умовах термобаричної інтенсифікації видобутку флюїду і бінарних технологій видобутку "флюїд – геотепло" уточнювати на 20-30% видобування тепла газоконденсатною свердловиною. Математична модель уточнює гирлові температури природного газу.
Моделювання ліфтингу теплоносія в геотермальній свердловині газоконденсатного родовища
Keywords: yield of geothermal fluid; thermal gradient; rock; parametric temperature full-scale; heat exchange coefficient; Joule-Thompson effect; дебіт геотермального флюїду; термічний градієнт; гірська порода; параметричне температурне поле; коефіцієнт теплообміну; ефект Джоуля-Томсона